PEMBUATAN BRIKET BERBAHAN LIMBAH KULIT KOLANG-KALING DI DESA JATIREJO GUNGPATI SEMARANG - Supriyadi, Supriyadi; Masturi, Masturi; Mahardika, P.A.; Pratiwi, D.J.; Susilo, Susilo (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2014)
Community service activities have been carried out with the caption Accompaniment Leather Processing fro Being Gunungpati Jatirejo village Briquette in Semarang. Background This village was chosen for the reason that it has expanded economic activity that produces a variety of snack food products that is characteristic of this village. Program-related community service activities above, the Physics Department has undertaken preparatory activities carried out in the laboratories of Physics. In this preparatory activities have made a molding tool briquettes, briquette press equipment for compacting, testing and analysis of samples. The next activity is the implementation of the results on the field were done with lectures and practical approach. The results of the activities in the field generally indicates that the participants can make some sample briquettes. However, to further the process has not been analyzed, considering the current conditions do not allow the activity to heat up with the sun because of the rain.